PENINGKATAN KETERAMPILAN PASSING BAWAH BOLA VOLI MELALUI MEDIA PEMBELAJARAN BOLA MODIFIKASI - Taufik Rihatno; Gunawan Gunawan (Gladi : Jurnal Ilmu Keolahragaan, 2018)
, The purpose of this research is to improve of forearm pass skill of volleyball through the modification ball learning media. The method that used in this research is action research. The research flow refers to the action research that proposed by Kemmis and Mc.Taggart. The result of this research showed seventeen from twenty students are able to do forearm well it is about 85%, While students who do not pass about three students it is about 15%. From this research, it can be conclude that through the modification ball learning media can improve forearm pass skill of volleyball significantly. Keyword: Passing, Volleyball, Learning, Modification.